(3GdefJNH ef cJGH (B"(3GdefJMd(B"s - (3eLghds
(3ChdgG (B:s
(3dCHi GdYdGA GdeYQi(B: (3EPG eG GdCQHYhf eVJ ceGdG aeG ai GdeQA ef COH HYjf s
(3BNQgG (B:s
(3dbGA GdeSGYi Cf jOhe dc GdeOi hYeQ GdeYGdi Cf jWhd dc GdYeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3cJGH GdefJMd dCHi efUhQ YHOGdedc Hf eMeO Hf ESeGYjd GdKYGdHis
(3GdeJhai (B429(3g`s
(3HgG fXGe GdJYbjHIs
(3JdGgG CTYGQ CNQi ai SHY hQbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdCOHs